Exposure to traffic-related air pollution and noise during pregnancy and childhood, and functional brain connectivity in preadolescents. (June 2022) - Pérez-Crespo, Laura; Kusters, Michelle S.W.; López-Vicente, Mónica; Lubczyńska, Małgorzata J.; Foraster, Maria; White, Tonya; Hoek, Gerard; Tiemeier, Henning; Muetzel, Ryan L.; Guxens, Mònica
Graphical abstract: Highlights: Exposure to NO2, NOx, and PM2.5abs was associated with higher brain connectivity. Increased functional connectivity was found between regions of different networks. Slightly more than half of the identified connections were intra-hemispheric. First years of life were periods of susceptibility to air pollution exposure. Road traffic noise exposure was not associated with functional brain connectivity. Abstract: Background: The amount of people affected by traffic-related air pollution and noise is continuously increasing, but limited research has been conducted on the association between these environmental exposures and functional brain connectivity in children. Objective: This exploratory study aimed to analyze the associations between the exposure to traffic-related air pollution and noise during pregnancy and childhood, and functional brain connectivity amongst a wide-swath of brain areas in preadolescents from 9 to 12 years of age. Methods: We used data of 2, 197 children from the Generation R Study. Land use regression models were applied to estimate nitrogen oxides and particulate matter levels at participant's homes for several time periods: pregnancy, birth to 3 years, 3 to 6 years, and 6 years of age to the age at magnetic resonance imaging (MRI) assessment. Existing noise maps were used to estimate road traffic noise exposure at participant's homes for the same time periods. Resting-state functional MRI was obtained at 9–12 years of age. Pair-wise correlation coefficients of the blood-oxygen-level-dependent signals between 380 brain areas were calculated. Linear regressions were run and corrected for multiple testing. Results: Preadolescents exposed to higher levels of NO2, NOx, and PM2.5 absorbance, from birth to 3 years, and from 3 to 6 years of age showed higher correlation coefficients among several brain regions (e.g. from 0.16 to 0.19 higher correlation coefficient related to PM2.5 absorbance exposure, depending on the brain connection). Overall, most identified associations were between brain regions of the task positive and task negative networks, and were mainly inter-network (20 of 26). Slightly more than half of the connections were intra-hemispheric (14 of 26), predominantly in the right hemisphere. Road traffic noise was not associated with functional brain connectivity. Conclusions: This exploratory study found that exposure to traffic-related air pollution during the first years of life was related to higher functional brain connectivity predominantly in brain areas located in the task positive and task negative networks, in preadolescents from 9 to 12 years of age. These results could be an indicator of differential functional connectivity in children exposed to higher levels of air pollution.